Strategi Penyampaian Pesan Dakwah Jama’ah Tabligh di Lingkungan Masjid Sumber Bungur Kecamatan Pakong Kabupaten Pamekasan - Ahmad Noval Romsi (Fakultas Dakwah IAIN Jember, 2021)
Some of today's Muslims often limit their perception of their religion as a physical identity. However the so-called identity itself has already deteriorated, only leaving their Islamic identity shown in the form of a single sheet of identity card. Such phenomenon is what causes the term